Bureaucracy, Situation, Discrimination, and Elite in Islamic Education Perspective of Digital Era - Badruzaman, Abad; Hosaini, Hosaini; Halim, Abdul (Bulletin of Science Education, 2023)
The article is to find out the definition and system of good and correct bureaucracy from an Islamic education perspective in the Digital Era. To find out the definition and practice of discrimination as well as solutions to deal with discrimination from an Islamic education perspective. To find out the definition of elite in the Islamic view of the digital era. The researchers engage in synthesizing the gathered information and conducting a thorough analysis. It presents this literature review within a descriptive qualitative research framework, adopting a phenomenological approach, to extract insights that address the research question by first collecting data and then seeking understanding. The result show that Discrimination can be overcome by instilling the teachings of the Islamic religion (caliphate principles) into oneself by accepting the nature of humans as social creatures who must live side by side with other humans who have different personalities and characteristics. At the elite level of thinking, we observe a pragmatic approach as elites gravitate toward populist figures to boost their popularity. This behavior is often characterized as a form of currying favor with those in power. The resulting phenomenon has generated narratives that have become a source of political turmoil, leading to widespread unrest among the grassroots population. Keywords: Elite in Digital Era, Discrimination in Digital Era, Bureaucracy in Digital Era